2000
DOI: 10.1159/000026431
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Leukocyte Distribution and Surface Expression of Adhesion Molecules Accompanied with Hypothalamically Induced Restlessness in the Cat

Abstract: One type of emotional behavior called restlessness occurs when the anteromedial hypothalamus is stimulated in cats. We examined the changes in the distribution and surface expression of adhesion molecules in leukocytes accompanied with restlessness. Mature female cats were used for this study. The cats were stimulated with 60 Hz sine wave train pulses (20–90 μA, 10 s in duration, at 5-min intervals) for 60 min. Samples of blood were collected from 30 min before stimulation up to several hours after the final s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
1
10
2
Order By: Relevance
“…In our previous study, we reported that AH stimulation induced changes in the leukocyte distribution and surface expression of adhesion molecules (Mori, Kaname, Sumida, Tanaka, Kubo, Tashiro, & Nomoto, 2000). Therefore, in our present study, we examined the relationship between VMH stimulation and changes in the leukocyte distribution and surface expression of adhesion molecules.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our previous study, we reported that AH stimulation induced changes in the leukocyte distribution and surface expression of adhesion molecules (Mori, Kaname, Sumida, Tanaka, Kubo, Tashiro, & Nomoto, 2000). Therefore, in our present study, we examined the relationship between VMH stimulation and changes in the leukocyte distribution and surface expression of adhesion molecules.…”
Section: Introductionmentioning
confidence: 83%
“…The methods employed in this study were almost the same as those used in our previous study (Mori, Kaname, Sumida, Tanaka, Kubo, Tashiro, & Nomoto, 2000). Therefore, the following paragraphs describe only the primary aspects of the methodology.…”
Section: Methodsmentioning
confidence: 99%
“…Hypothalamic stimulation was given to each cat at 5-min intervals for 60 min, and then the cat turned off the stimulation within 2.0 s for a total of 12 stimulations. The times and intervals of stimulation were the same as those employed in our previous study [31].…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral blood was sampled from the external jugular vein without anesthesia while the neck of the cat was held gently [31]. Soon after the collection of peripheral blood, both catecholamine and cortisol assays were performed.…”
Section: Collection and Treatment Of Blood Samplesmentioning
confidence: 99%
See 1 more Smart Citation